PERUMUSAN STRATEGI PENINGKATAN MUTU TEKNIK PRODUKSI IKAN GURAMI (Osphronemus gouramy) BERDASARKAN METODE FORCE FIELD ANALYSIS (FFA) - Uyun Erma Malika; Tejasari Tejasari; Evita Soliha Hani (University of Jember, 2012)
Carp (Osphronemus gouramy) is one kind of freshwater fish that can be farmed in the pond. This research was conducted to: (a) evaluate the quality of carp farming technique of segmentations of seeding, nursery, and growing based on SNI: 01-6485.3-2000 (standard production of carp seeding and nursery) and SNI: 01-7241-2006 (standard production of carp growing segment in the pond), (b) analyze the cost efficiency of carp farming in each segmentation, (c) formulate development strategies of carp cultivation techniques in each segment. Research area was determined by purposive method. The research applied descriptive method, and sampling was conducted by snowball sampling of 16 respondents. Data were analyzed by calculating the percentage of the conduct of cultivation technique quality, R/C ratio, and Force Field Analysis (FFA). The results of evaluation of the quality of cultivation techniques showed that the percentage of production quality conduct level of carp production for the segmentation of growing at pre-production stage was 53.67%, at production stage was 60.00%, and at harvesting stage was 70.00%. Meanwhile, at seeding segment, the percentage of production quality was 67.20%, at production stage was 63.70%, and at harvesting stage was 68.70%. R/C ratio in growing segment was 1.39 and in seeding segment was 1.48, which means that both of the segments of carp farming were feasible to manage. Based on FFA analysis, the strategies that need to be done are conducting human resource empowerment (farmers) by appropriate technology innovations, institutional strengthening of farmer groups, conserving natural resources, and improving cooperation between farmers with local marine and fisheries department. Keywords: Strategy, carp (Osphronemus gouramy), quality, Force Field Analysis (FFA)